Pioglitazone - the forgotten drug with multidirectional action - Aab, Arkadiusz; Zarańska, Julia (Journal of Education, Health and Sport, 2023)
Introduction: Pioglitazone (PG) which belongs to thiazolidinedione class is a drug used in the treatment of type 2 diabetes. PG increases the insulin sensitivity of peripheral tissues. Type 2 diabetes mellitus (T2DM) is one of the most common and fastest developing diseases. The antihyperglycemic effect of pioglitazone (PG) is not its only one. This drug has a number of other metabolically beneficial effects. Many outcome trials indicate a positive impact of PG on the functioning of other systems. Aim of the study: The aim of this study is to summarize the current knowledge on the effectiveness and safety of pioglitazone based on the available scientific literature. Materials and methods: Literature review based on PubMed, Google Scholar database using the following phrases: pioglitazone, type 2 diabetes, pioglitazone in non-alcoholic fatty liver disease (NAFLD) therapy, pioglitazone and cardiovascular risk, pioglitazone nephroprotective effect, pioglitazone safety profile. State of knowledge: Pioglitazone is an oral antidiabetic drug used in the therapy of T2DM. PG belongs to the ‘insulin- sensitizers’. It is included in the treatment in the case of intolerance, contraindications to metformin or as part of combination therapy. Conclusions: Recently, interest in pioglitazone has waned due to the perception of significant side effects. The analysis of the papers showed a positive effect of PG on the cardiovascular system, central nervous system, NAFLD and nephroprotection. The acceptable safety profile of pioglitazone with the appropriate selection of patients as well as its multidirectional action and effectiveness mean that clinicians should reconsider the use of this drug guided by the balance of profits and losses.